2016
DOI: 10.1161/strokeaha.116.015200
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Calcification and Risk of Stroke

Abstract: Information on cardiovascular risk factors was obtained by interview, physical examination, and blood sampling. Background and Purpose-It remains uncertain whether aortic valve calcification (AVC) is a risk factor for stroke. Methods-From the population-based Rotterdam Study, 2471 participants (mean age: 69.6 years; 51.8% women) underwent computed tomography to quantify AVC. We assessed prevalent stroke and continuously monitored the remaining participants for the incidence of stroke. Logistic and Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Intracranial carotid artery calcification (ICAC) and vertebrobasilar artery calcification (VBAC) were quantified using a semiautomatic scoring method that allows to manually segment calcification in each consecutive CT slice after which the calcification volume is computed using the pixel size and the increment [ 2 , 19 , 20 ]. A detailed description of the evaluation methods is provided elsewhere [ 2 , 3 , 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intracranial carotid artery calcification (ICAC) and vertebrobasilar artery calcification (VBAC) were quantified using a semiautomatic scoring method that allows to manually segment calcification in each consecutive CT slice after which the calcification volume is computed using the pixel size and the increment [ 2 , 19 , 20 ]. A detailed description of the evaluation methods is provided elsewhere [ 2 , 3 , 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Main findings in recent years with respect to stroke and Alzheimer’s disease, include the study of the following determinants: cerebral perfusion [ 252 ], thyroid function [ 189 ], aortic valve calcification [ 253 ], white matter microstructure [ 254 ], orthostatic hypotension [ 255 ], mid-life blood pressure [ 256 ], depression [ 257 ], and parental family history [ 258 ].…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Important new reports describe the determinants of overall plaque burden and how plaque composition relates to a history of stroke [ 465 , 466 ]. In recent years, we have expanded our interest in imaging markers of cardiovascular disease towards epicardial fat [ 467 , 468 ] and aortic valve calcification [ 253 , 469 ].…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Progression of AVC is not significantly associated with stroke but with progression of mitral annular calcification (MAC) [53]. Other studies showed that there is no association between AVC and increased risk of stroke [54] or dementia [55]. Adler et al [56] in their study confirmed that presence of AVC increases odds of death from CVD causes.…”
Section: Discussionmentioning
confidence: 93%